Effects of Velocity-Slip and Viscosity Variation in Squeeze Film Lubrication of Two Circular Plates - R.R. Rao; K. Gouthami; J.V. Kumar (Tribology in Industry, 2013)
A generalized form of Reynolds equation for two symmetrical surfaces is taken by considering velocity-slip at the bearing surfaces. This equation is applied to study the effects of velocity-slip and viscosity variation for the lubrication of squeeze films between two circular plates. Expressions for the load capacity and squeezing time obtained are also studied theoretically for various parameters. The load capacity and squeezing time decreases due to slip. They increase due to the presence of high viscous layer near the surface and decrease due to low viscous layer.